Onobrychis silvanensis sp. nov., a new Fabaceae (sect. Hymenobrychis) taxon from Turkey - Aytac, Zeki; Rabaute, Philippe; Coulot, Pierre (Phytotaxa, 2020)
Onobrychis silvanensis sp. nov., is described from Silvan, Diyarbakır province, in southeastern Anatolia, Turkey. The new species is closely related to O. galegifolia and O. radiata. The white corolla feature of O. silvanensis is uncommon in Turkish Onobrychis species and is otherwise known only in O. haussknecthii and O. hypargyrea. In addition to the diagnosis and taxonomic description, morphological characters of both flowering and fruiting O. silvanensis plants are presented. Distribution maps for O. silvanensis, O. galegifolia and O. radiata in Turkey are also provided. Although currently Data Deficient by IUCN status criteria, we anticipate O. silvanensis constitutes a candidate for Endangered status.